Mechanical anisotropy of a two-phase composite consisting of aligned elliptical inclusions - Dabrowski, M.; Schmid, D. W. (TRABAJOS DE GEOLOGÍA, 2009)
The shape preferred orientation of rock constituents results in an overall mechanical anisotropy. A differential effective medium (DEM) type of scheme predicting the effective anisotropic viscosity of a composite consisting of aligned elliptical inclusions is proposed and validated by finite element modeling. A comparison with an existing self-consistent averaging (SCA) scheme is given and the DEM scheme is shown to provide an improved estimate of the effective normal and shear viscosity for high inclusion concentrations.